Java and Bolaang Mongondow Social Relationship - Chaterina P. Doni; Dahlia Husain (Journal of Public Representative and Society Provision, 2022)
This study aims to determine the Social Relations of the Javanese and Bolang Mongondow ethnic communities. This research uses qualitative methods with a descriptive approach. Collecting data on research through direct interviews with informants. The results of this study show that the Javanese and Bolaang Mongondow ethnic communities have had a close relationship through various media such as trade, migration, and various phenomena in the community. The nature of harmony in this multi-ethnicity causes inter-ethnic life to have an open, democratic, tolerant nature, and a willingness to coexist in differences. The relationship between Javanese ethnicities and Bolaang Mongondow is a miniature that has social harmony in Indonesia from the reality of a heterogeneous society that is often hit by waves of social disintegration.